Use of Complementary and Alternative Medicine by Oncology Patients in the City of Bucaramanga, Colombia - Nicolás Martínez-Ramos; Norma Cecilia Serrano Díaz; Claudia Janeth Uribe-Pérez; Doris Cristina Quintero-Lesmes; Carolina Mariño-Manrique; Raúl Murillo (Revista de Investigación e Innovación en Ciencias de la Salud)
Introduction. Complementary and alternative medicine (CAM) is frequently used by oncology patients worldwide, often alongside conventional treatments. Understanding the frequency of use and motivations for CAM use is essential to improve patient-centered cancer care and guidance.